Evaluation of chronological age based on third-molar development in the Serbian population - Filipović, Gordana; Djordjević, Nadica S.; Stojanović, Nikola M.; Brkić, Zlata; Igić, Marija; Marjanović, Dragan; Šehalić, Meliha (Vojnosanitetski pregled, 2021)
Background/Aim. Persons identification and their age assessment is necessary in vast number of cases and there are different methods used for such purposes. Numerous studies indicate that the third molar development could play a crucial role in identifying an individual`s age. The aim of this study was to determine the possibility for estimating the chronological age based on the third molar development stages in children and young adults in the Serbian population. Methods. A total of 570 Serbian patients aged 6–27 years were included in this study. Out of the total number of subjects, there were 248 males with an average age of 12.21 ± 3.91 years, and 332 females with an average age of 12.88 ± 4.06 years. Stages of dental formation were determined on orthopantomograms by comparing with standard Demirjian radiographic appearances. Results. Third molars mineralization occured more rapidly in males than in females. Most of the persons with third molar (the stage H development according to the Demirjian method) were older than 18 years. Conclusion. Тhird molar mineralization stages determination on orthopantomograms is useful additional method for determination of chronological age in living individuals. This finding might be important for forensic studies, focusing on the determination of the legally important ages. Variability among different ethnic groups has to be taken into consideration when applying this method. It is necessary to carry out extensive surveys on a larger sample in order to determine the norms for assessing the dental and chronological age of Serbian population.
Keywords: adolescent; age determination by teeth; child; forensic dentistry; molar, third; radiography, dental; serbia